The Influence of Leadership, Personality, Competence, and Spirituality on Employee Performance Bogor Islamic Hospital - Wijaya, Gumelar Adi; Indupurnahayu; Putra, Awang Darmawan; Sofianti, Evin (PT FORMOSA CENDEKIA GLOBAL, 2024)
Three aspects of intelligence are intellectual intelligence by optimizing their intellect, emotional intelligence by building feelings and desires in order to encourage individuals to always be better, and spiritual intelligence by building strong faith so that they have high productivity. This study aims to analyze the influence of leadership, personality, competence, and spirituality on the performance of Bogor Islamic Hospital employees. This study used quantitative methods using questionnaires as a data collection tool from 80 respondents with various employee characteristics. Based on the results of the analysis, it is known that the significance value for the influence of X1, X2, X3, and X4 on Y is 0.000 < 0.05 and the F value is calculated at 84.149 > F table 2.490 so that it can be concluded that H5 is accepted which means that the influence of leadership, personality, competence, and spirituality simultaneously affects the performance of Bogor Islamic Hospital employees. The managerial implications of this study are that it can prove empirically the influence of leadership, personality, competence and spirituality on employee performance and as a reference in designing strategies and decision-making processes in hospital development.